Penerapan Algoritma Dynamic Programing pada Pergerakan Lawan dalam Permainan Police and Thief - Insidini Fawwaz; Agus Winarta (Universitas Medan Area, 2019)
Games have the basic meaning of games, games in this case refer to the notion of intellectual agility. In its application, a Game certainly requires an AI (Artificial Intelligence), and the AI used in the construction of this police and thief game is the dynamic programming algorithm. This algorithm is a search algorithm to find the shortest route with the minimum cost, algorithm dynamic programming searches for the shortest route by adding the actual distance to the approximate distance so that it makes it optimum and complete. Police and thief is a game about a character who will try to run from police. The genre of this game is arcade, built with microsoft visual studio 2008, the AI used is the Dynamic Programming algorithm which is used to search the path to attack players. The results of this test are police in this game managed to find the closest path determined by the Dynamic Programming algorithm to attack players